THE NATURE AND IMPACT OF THE SUPERVISORY BEHAVIOURS OF SCHOOL HEADS ON THE CULTURE OF TEACHING AND LEARNING - Mohammed, Issah; Nurudeen, Fuseini; Suhiyini, B. H. Adam (International Journal of Research -GRANTHAALAYAH, 2025)
The study adopted the constructivist philosophical assumptions in examining the nature and impact of the supervisory behaviours of junior high school head teachers on the culture of teaching and learning within the Sagnarigu Municipality, Tamale, Ghana. A case study research design was employed along with the qualitative research approach. The study’s population comprised all the junior high school head teachers and teachers under the Sagnarigu Municipality. The convenience sampling technique was used to select twenty (20) teachers and ten (10) head teachers, making a sample size of thirty (30) participants. Face-to-face in-depth individual interviews were conducted using open-ended questions. Ten (10) head teachers and twenty (20) teachers were chosen from ten (10) junior high schools in the Sagnarigu Municipality using a convenient sampling approach. The total sampling size was thirty (30) participants. Permission to conduct the study was sought from the Municipal Education Office. Data were collected through face-to-face in-depth individual interviews using the Pen-and-Paper Personal method. The collected data were analysed using a thematic analytical method.